2002
DOI: 10.1067/mcp.2002.127113
|View full text |Cite
|
Sign up to set email alerts
|

Atovaquone plus chloroguanide versus mefloquine for malaria prophylaxis: A focus on neuropsychiatric adverse events*

Abstract: Prophylactic use of mefloquine was associated with significantly higher scores on scales for depression, anger, and fatigue and lower scores for vigor than prophylactic use of atovaquone plus chloroguanide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 14 publications
0
27
0
2
Order By: Relevance
“…15,17,30 Contrary to our findings, other studies have reported an association between NPOs and mefloquine. 6,10,11,13,[31][32][33] The study by Schlagenhauf and others was a randomized, double-blinded study among travelers and found mefloquine to have the highest proportion of moderate to severe NPOs compared with chloroquine/proguanil, doxycycline, and A/P. 6 However, this study had small numbers and the outcomes were defined by a subjective questionnaire as opposed to medical diagnoses of the outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,17,30 Contrary to our findings, other studies have reported an association between NPOs and mefloquine. 6,10,11,13,[31][32][33] The study by Schlagenhauf and others was a randomized, double-blinded study among travelers and found mefloquine to have the highest proportion of moderate to severe NPOs compared with chloroquine/proguanil, doxycycline, and A/P. 6 However, this study had small numbers and the outcomes were defined by a subjective questionnaire as opposed to medical diagnoses of the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Studies evaluating the occurrence of neuropsychiatric outcomes (NPOs) after mefloquine use report mixed results, but a large proportion of these studies found an association between mefloquine and NPOs. [7][8][9][10][11][12][13][14][15][16][17] Due to the extensive use of mefloquine for malaria prevention among service members before 2009 and its continued, limited use, after that point, the need to evaluate adverse events in service members who took the drug is evident. Therefore, a retrospective population-based cohort study was conducted among service members.…”
Section: Introductionmentioning
confidence: 99%
“…There was a further potential source of bias in that, except for two trials, 20,26 all the trials in this review were funded wholly or in part by drug companies. The exact nature of this funding was not always clear or available.…”
Section: 20mentioning
confidence: 99%
“…17,20,21 interventions Atovaquone-proguanil was compared against doxycycline in one trial, 27 and against mefloquine in three trials. 24,26,27 Doxycycline was compared against mefloquine in three trials. 17,21,27 Four trials compared any of the above drugs against chloroquine-proguanil.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation